2009
DOI: 10.1002/hlca.200800275
|View full text |Cite
|
Sign up to set email alerts
|

New Stilbene, Benzofuran, and Coumarin Glycosides from Morus alba

Abstract: Five new compounds, including three new stilbene-derived glycosides, one novel arylbenzofuran derivative, and one new coumarin glycoside, along with ten known compounds were isolated from the H 2 O extract of the bark of Morus alba L. The new compounds were assigned to the structures of 4'-O-b- (5) by spectroscopic means, and acid and enzymatic hydrolyses. Three compounds, 2'- (8), and 6,7-dihydroxycoumarin 7-(6-O-a-rhamnopyranosyl-b-d-glucopyranoside) (9), were found for the first time in Morus alba.Introduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…The root bark, named Sang-BaiPi, has been used for treating diabetes, relieving asthma, and protecting the liver (Ahn 2012). Phytochemical studies on Sang-Bai-Pi extracts resulted in the isolation of phenolic compounds including isoprenylated flavonoids (Jiang et al 2003), Diels-Alder type adducts (Hano et al 1988), triterpenoids (Jung et al 2014), coumarins (Piao et al 2009), benzofurans (Piao et al 2009), and stilbenes (Piao et al 2009), which were reported to show anti-oxidant , tyrosinase inhibitory (Lee et al 2004), anti-inflammatory (Yang et al 2011), anti-hepatitis B virus (Geng et al 2012), anti-cancer (Dat et al 2010), and antimicrobial (Naik et al 2015) activities. The EtOAc soluble Electronic supplementary material The online version of this article (doi:10.1007/s12272-015-0613-8) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 98%
“…The root bark, named Sang-BaiPi, has been used for treating diabetes, relieving asthma, and protecting the liver (Ahn 2012). Phytochemical studies on Sang-Bai-Pi extracts resulted in the isolation of phenolic compounds including isoprenylated flavonoids (Jiang et al 2003), Diels-Alder type adducts (Hano et al 1988), triterpenoids (Jung et al 2014), coumarins (Piao et al 2009), benzofurans (Piao et al 2009), and stilbenes (Piao et al 2009), which were reported to show anti-oxidant , tyrosinase inhibitory (Lee et al 2004), anti-inflammatory (Yang et al 2011), anti-hepatitis B virus (Geng et al 2012), anti-cancer (Dat et al 2010), and antimicrobial (Naik et al 2015) activities. The EtOAc soluble Electronic supplementary material The online version of this article (doi:10.1007/s12272-015-0613-8) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 98%
“…The root barks of mulberry trees are named ''SangBai-Pi'' and are used for a variety of medicinal purposes, primarily in South Asia. Previously, many phytochemical compounds such as flavonoids, Diels-Alder type adducts, coumarins, stilbenes, and triterpenoids (Hano et al 1988;Piao et al 2009;Jung et al 2014) have been isolated from the root bark of M. alba. These compounds have been reported to show anti-oxidant, anti-inflammatory, anticancer, and anti-microbial activities (Dat et al 2010;Yang et al 2011;Yang and Lee 2012;Naik et al 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, extracts of M. alba were shown to be potent antioxidants and prevented doxorubicin cardiotoxicity (Wattanapitayakul et al 2005). In this paper, we depicted the isolation and identification of a new biphenyl-furocoumarin, named morescoumarin A (1), a new prenylated flavanone, named morflavanone A (2), and five known compounds, moracin M (3) (Zhang et al 2009), moracin M-3′-O-β-D-glucopyranoside (4) (Basnet et al 1993), moracin M-6-O-β-D-glucopyranoside (5) (Piao et al 2009), mulberroside F (6) (Hano et al 1997). Structures of new compounds were characterised by 1 H NMR, 13 C NMR, 2D NMR, HR-ESI-MS and CD data.…”
Section: Introductionmentioning
confidence: 99%